Optimal forward contracting in LNG supply capacity investment - Suenaga, Hiroaki (IAEE, 2007)
This paper contructs a stylized model of an LNG producer's decision on the level of committment to long-term supply arrangement. The model extends a conventional two-stage model of optimal hedging by accomodating two features commonly observed with LNG trading practice: (1) the forward price of LNG is stochastic at the time of forward contracting as it is linked to the spot price of an alternative fuel, namely crude oil, and (2) the producer has a choice over multiple regional gas markets to which it supplies LNG in short-term trading. The model also allows the producer to hedge its price risk through furtures markets of related energy commodities.For the second feature, a numerical example is provided to illustrate the distributional properties of the maximum of the regional spot prices and how changes in the stochastic properties of one regional (i.e., US) gas price affect the firm's optimal forward position. For range of sensible parameter values, an increase in mean price in one regional market always increases the expected value of the maximum price. These two changes, as observed in the US, affect the firm's forward position in opposite ways. The net effect is indeterminate. These results imply that the transition from a conventional trading model through long-term supply-purchase agreement to more flexible short-term trade will be gradual and decelerated by high volatile regional price differentials-what has been motivating recent discussions on potential returns from spot LNG trading.